2018
DOI: 10.1093/ofid/ofy218
|View full text |Cite
|
Sign up to set email alerts
|

Bezlotoxumab Is Associated With a Reduction in Cumulative Inpatient-Days: Analysis of the Hospitalization Data From the MODIFY I and II Clinical Trials

Abstract: BackgroundPatients with recurrent Clostridium difficile infection (rCDI) are more likely to have a hospital readmission and spend increased time in inpatient settings compared with patients with primary CDI. MODIFY I and II demonstrated that bezlotoxumab significantly reduced rCDI vs placebo. A post hoc within-trial analysis assessed whether bezlotoxumab was associated with a reduction in cumulative inpatient-days.MethodsData were pooled from the MODIFY trials to estimate the cumulative hospitalized days summe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…In 382 MODIFY I/II participants with cancer, the proportion of patients developing rCDI was lower in the bezlotoxumab (26/146, 17.8%) than the placebo arms (42/138, 30.4%), with an absolute difference of -12.6%, 95% CI -22.5 to -2.7 [62]. As shown in another analysis, the mean cumulative inpatient-days were lower in the bezlotoxumab (12.1 days) than the placebo arms (14.1 days), with a mean difference of -2.1 days (95% CI -3.7 to -0.4) [63]. An exploratory study investigated if human genetic variations are able to influence the effect of bezlotoxumab in patients enrolled in the MODIFY trials.…”
Section: Efficacy Of Bezlotoxumab In Phase 3 Rctsmentioning
confidence: 69%
“…In 382 MODIFY I/II participants with cancer, the proportion of patients developing rCDI was lower in the bezlotoxumab (26/146, 17.8%) than the placebo arms (42/138, 30.4%), with an absolute difference of -12.6%, 95% CI -22.5 to -2.7 [62]. As shown in another analysis, the mean cumulative inpatient-days were lower in the bezlotoxumab (12.1 days) than the placebo arms (14.1 days), with a mean difference of -2.1 days (95% CI -3.7 to -0.4) [63]. An exploratory study investigated if human genetic variations are able to influence the effect of bezlotoxumab in patients enrolled in the MODIFY trials.…”
Section: Efficacy Of Bezlotoxumab In Phase 3 Rctsmentioning
confidence: 69%
“…The greatest reduction in inpatient days (−3.5 days) was observed in participants who presented with severe CDI at study entry. These results show promise for BEZ to reduce inpatient days, particularly for those with multiple risk factors for rCDI [ 38 ].…”
Section: Trials Not Included In the 2021 Focused CDI Guideline Updatementioning
confidence: 99%
“… 35 Furthermore, a post hoc analysis of hospitalization data from both MODIFY 1 and 11 trials showed that bezolotoxumab also resulted in reduction in cumulative inpatient days and CDI-associated re-hospitalizations. 36 , 37 …”
Section: Fecal Microbiota Transplant and Bezlotoxumabmentioning
confidence: 99%